2018
DOI: 10.1097/mrr.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

The baseline speed of 10-m gait predicts ambulatory discharge for hospitalized frail elderly after DOPPO rehabilitation

Abstract: The discharge of elderly patients from hospital on the basis of their independent gait program (DOPPO) is a new rehabilitation strategy for physically frail hospitalized elderly that aims to recover independent gait and to achieve ambulatory discharge. We retrospectively investigated baseline determinants of physical measures associated closely with the 6-min walking distance (6MWD) after DOPPO. Participants were 137 consecutive elderly inpatients, irrespective of the causative disease (mean age: 82±7 years; 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…ADL scores on admission were particularly low in the very elderly patients, with 67.9% unable to walk unaided and 77.2% unable to use the toilet independently; self-care was highly infeasible. These facts suggest that the elderly patients with HF essentially require disease management and personalized care support, possibly achieved by comprehensive rehabilitation [16].…”
Section: Discussionmentioning
confidence: 99%
“…ADL scores on admission were particularly low in the very elderly patients, with 67.9% unable to walk unaided and 77.2% unable to use the toilet independently; self-care was highly infeasible. These facts suggest that the elderly patients with HF essentially require disease management and personalized care support, possibly achieved by comprehensive rehabilitation [16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, exercise therapy has been shown to improve physical function, 6MWD, and the Short Physical Performance Battery in frail patients. [19][20][21] Furthermore, recent studies in Japan have suggested that a 3-month CR program for frail older adults with cardiovascular disease may significantly improve walking speed, grip strength, and lower limb muscle strength. 22 In the present study, a significant improvement in 6MWD at the end of CR was also observed, suggesting that a CR program that includes exercise therapy improves exercise tolerance in frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…addition, in older patients with heart disease, usual gait speed and 6MWD show a strong positive correlation, 159,160 and the prognostic value is also reported to be similar. 159 ▋ 3.2.2 Significance and Effectiveness (Table30)…”
mentioning
confidence: 90%